PENERAPAN AKSARA JAWA PADA BANGUNAN CAGAR BUDAYA DAN OBJEK WISATA DI KAWASAN SUMBU FILOSOFI YOGYAKARTA - Agyl Fathu Rochim; Nur Hidayati; Ghis Nggar Dwiadmojo (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2026)
Aksara Jawa as one of the cultural heritages of the Javanese people is now increasingly rarely used in everyday life. This problem encourages the importance of preservation efforts, one of which is through utilization in public spaces, especially in the Yogyakarta philosophical axis area which is rich in cultural values. This study aims to examine the application of aksara Jawa in cultural heritage buildings and tourist attractions along the Yogyakarta philosophical axis, as well as to examine its relevance to values of Keyogyakartaan. The study uses a qualitative descriptive approach with field observation techniques, in-depth interviews, and visual documentation. The results of the study show that the use of aksara Jawa has been applied to nameplates, location markers, and decorative elements in historic buildings such as the Yogyakarta Palace, Tugu Pal Putih, Yogyakarta Station, and several points in Malioboro. However, its use still contains spelling errors and inconsistencies in the rules of aksara Jawa writing. These findings indicate that preservation has not been carried out optimally and tends to be only aesthetic. The values of Yogyakarta such as "pamenthanging gandewa, pamanthenging cipta" and "sawiji, greget, sengguh ora mingkuh" can be used as a basis for strengthening more meaningful preservation. The conclusion of this study is the need for standardization of aksara Jawa writing in public spaces as part of educative and representative cultural preservation. It is recommended that the government, academics, communities and society collaborate in compiling standard guidelines and increasing cultural literacy through strategic spaces.